2020
DOI: 10.4103/tjo.tjo_110_18
|View full text |Cite
|
Sign up to set email alerts
|

Short-term refractive and ocular parameter changes after topical atropine

Abstract: PURPOSE: The purpose of this study is to explore short-term refractive and ocular parameter changes and their correlations after cycloplegia with atropine. METERIALS AND METHODS: This is a prospective clinical trial that enrolled 96 eyes of 96 participants (mean age, 8.5 ± 2.1 years). Spherical equivalent refractive error (SER), axial length (AL), mean keratometric value (mean-K), anterior chamber depth (ACD), and intraocular pressure (IOP) were measured at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…We found that AL was controlled and even shortened within 4.8 months of treatment in the treated eye. This observation is consistent with that of previous studies, although the mechanism remains unclear 5 , 14 , 15 . However, since we cannot exclude data for the first 4.8 months given the retrospective nature of our study, we acknowledge that we may have overestimated the AL-retarding effect of atropine by using the outcome measure of the calculated annual changes in AL from short-term measurement of AL in some cases.…”
Section: Discussionsupporting
confidence: 94%
“…We found that AL was controlled and even shortened within 4.8 months of treatment in the treated eye. This observation is consistent with that of previous studies, although the mechanism remains unclear 5 , 14 , 15 . However, since we cannot exclude data for the first 4.8 months given the retrospective nature of our study, we acknowledge that we may have overestimated the AL-retarding effect of atropine by using the outcome measure of the calculated annual changes in AL from short-term measurement of AL in some cases.…”
Section: Discussionsupporting
confidence: 94%
“…The recruitment duration (X15) and total duration (X8) are significant factors predicting endpoint IOP. The recruitment duration (X15), one year before the termination of data collection, reflects the frequency and number of visits, which is indicative of a patient’s approach to medical care [ 30 , 31 , 32 ]. Because only for eyes were not prescribed atropine during recruitment, data from the recruitment duration can be considered as being from patients that had been taking atropine during the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term atropine application has raised concerns among some ophthalmologists [ 27 , 28 , 29 ]. Atropine can paralyze the pupillary muscle, increasing resistance and impeding the flow of the aqueous humor, which might increase intraocular pressure (IOP) [ 30 , 31 , 32 , 33 ]. We aimed to identify factors that predict incident IOP in patients with myopia after atropine use.…”
Section: Introductionmentioning
confidence: 99%
“…AL shortening not only occurs in LLRL treatment, but also in the treatment of atropine or orthokeratology lens. [36][37][38][39] Anatomically, an increase in ChT mechanically pushes the retina forward, which naturally shortens the AL. 32,40 Moreover, the choroid is a highly vascularized tissue, and changes in the ChBF may affect the AL.…”
Section: Discussionmentioning
confidence: 99%